2012
DOI: 10.1177/0143831x12438234
|View full text |Cite
|
Sign up to set email alerts
|

The impact of perceived organizational support on work–family conflict: Does role overload have a mediating role?

Abstract: The present cross-sectional study aims to investigate (1) the direct effects of perceived organizational support and role overload on work-family conflict and (2) the mediating role of role overload in the relationship between perceived organizational support and work-family conflict using a Turkish sample. The hypotheses were tested with a sample of 344 employees from small and medium-sized enterprises in Turkey. The results demonstrated that perceived organizational support was negatively related to both fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 59 publications
4
29
0
1
Order By: Relevance
“…Besides, this research found that POS also reduced work-family conflict and job burnout. The negative relationship among POS, work-family conflict and turnover intention was consistent in relation to the previous researches of Marchand and Vandenberghe [88], Gurbuz, Turunc and Celik [86] and Caesens, Stinglhamber, Demoulin and De Wilde [87]. POS were key mechanisms in connecting voluntary turnover among employees.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Besides, this research found that POS also reduced work-family conflict and job burnout. The negative relationship among POS, work-family conflict and turnover intention was consistent in relation to the previous researches of Marchand and Vandenberghe [88], Gurbuz, Turunc and Celik [86] and Caesens, Stinglhamber, Demoulin and De Wilde [87]. POS were key mechanisms in connecting voluntary turnover among employees.…”
Section: Discussionsupporting
confidence: 89%
“…Hypothesis 10: The results showed that perceived organizational support had a negative and significant relationship with work-family conflict, (p-value = 0.000 and beta coefficient = −0.600) ( Table 5). The result indicated that the more perceived organizational support, the greater the possibility that bankers will have low levels of work-family conflict, which was consistent with the findings of Gurbuz, Turunc, and Celik [86]. Thus, Hypothesis 10 was supported.…”
Section: Research Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…In a more recent study, Gurbuz et al . () confirmed that POS had a negative relationship with WFC (measured with the Netemeyer et al . scale ), while role overload did not have a mediating effect on the relationship between POS and WFC.…”
Section: Theoretical Backgroundsupporting
confidence: 53%